Chlorfenapyr containing anions uptake from industrial wastewater by ethylene glycol functionalized benzyl dimethyl tetradecyl ammonium bromide membrane. (15th April 2021) - Younas, Asma; Rashid, Hafiza Nadia; Hussain, Dilshad; Naqvi, Sayed Tayyab Raza; Khan, Muhammad Ali; Fatima, Batool; Majeed, Saadat
Abstract: The preservation of water and wastewater treatment has become a global challenge. The concentration of anions such as chlorides, fluorides, cyanides, and perchlorates above the permitted levels in water is harmful to human and aquatic life. Chlorfenapyr is an insecticide that contains the aforesaid anions and is abundantly present in industrial wastewater. This research is focused on the removal of these anions from wastewater by ethylene glycol functionalized benzyl dimethyl tetradecyl ammonium bromide immobilized on soluble polymer anion exchange membrane. The real wastewater samples rich in chlorfenapyr from two different sources (industrial and pond) were analyzed. Membrane efficiency was more than 50 ppm for each anion in a single fold. The double folds of membrane showed enhanced uptake and separation efficiency for chloride, fluoride, and cyanide from wastewater samples between 0.01 and 0.02 ppm down to lethal concenetrations values (LD 50). The membrane shows maximum separation efficiency between the pH ranges of 6–7. The interference effect on membrane separation efficiency showed that the replacement ability of sample anions was in the order of fluoride > chloride > perchlorate > cyanide. This high replacement efficiency of fluoride and chloride is attributed to the more chemical interactions of these anions with membrane. Graphical abstract: Image 1 Highlights: Chlorfenapyr analysis and detection from wastewater. Anion exchange membrane selectively helps the removal of anions from wastewater. Waste water from the pesticide industries largely affect aquatic and human life by affecting metabolic pathways in the body.